Um estudo sobre a abordagem dos conteúdos estatísticos em cursos de Licenciatura em Matemática: uma proposta sob a ótica da ecologia do didático - Goulart, Amari (2015)
The purpose of this study was to identify the relationships operating between the teaching of Statistics to Basic Education students (up to the 12th grade) and the teaching of Statistics at Teaching Degree programs in Mathematics relationships that might enhance the professional education of Brazilian teachers towards the development of Statistical Literacy among their future students. The Anthropological Theory of the Didactic, in its ecological perspective, was the theoretical framework adopted, from which two ecosystems were hypothesized: those of Mathematics teaching in Basic Education and in Teaching Degree programs in Mathematics. To examine whether these ecosystems are currently promoting the development of Statistical Literacy, the following documents were analyzed: the National Curriculum Parameters (PCN) for 6th-9th Grades (Mathematics), the PCN for 10th-12th Grades (Natural Sciences, Mathematics, and their Technologies), the PCN+ (Natural Sciences, Mathematics, and their Technologies), the Curriculum Guidelines for 10th-12th Grades (Natural Sciences, Mathematics, and their Technologies), the National Curriculum Guidelines for Mathematics Programs Teaching and Non-Teaching Degrees (DCN-BL), and the National Curriculum Guidelines for Higher-Education Training of Teachers for 1st-12th Grades Full Teaching Degree (DCN-FP). The following national exams were also evaluated: SAEB, Prova Brasil, ENEM, and ENADE. The analysis also included two textbook series (one for 6th-9th grades and the other for 10th-12th grades) approved by the National Textbook Program for Basic School (PNLD). The analyses of these documents and materials revealed that neither ecosystem currently promotes the development of Statistical Literacy. Between the teaching of Statistics to Basic Education students and the teaching of Statistics at Teaching Degree programs in Mathematics, no relationships were found to operate which might enhance the professional education of teachers towards the development of Statistical Literacy among their future students